IMPLEMENTATION OF MAINTENANCE SCENARIO FOR CRITICAL SUBSYSTEM IN AIRCRAFT ENGINE Case study: NTP CT7 engine - Fransiskus Tatas Dwi Atmaji; Anna Annida Noviyanti; Widia Juliani (School of Industrial and System Engineering, Telkom University, 2018)
An aircraft company needs to